Emissions vs. Earnings: Assessing the Financial Effects of Carbon Footprint in Malaysia’s Manufacturing Sector - khairunnisa, Ibrahim; Abu Hassan, Md. Isa; Mohamad, Jais; Dzulzalani, Eden (Journal of Information Systems Engineering and Management, 2025)
Introduction: Environmental sustainability is a critical concern, requiring enterprises to be accountable for carbon emissions. While existing research focuses on the energy sector, the manufacturing industry in Malaysia remains underexplored. Businesses are driven to reduce emissions by regulatory mandates and market expectations, often benefiting from improved financial performance Objectives: This study investigates the sustainability practices of manufacturing firms listed on Bursa Malaysia and their impact on financial performance. Methods: Using a random effects model, the study evaluates the relationship between carbon footprint and financial metrics, including Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI). Results: The findings indicate that the null hypotheses for these financial indicators are accepted, suggesting no significant impact. Conclusions: These insights highlight the need for more comprehensive strategies to enhance environmental and financial outcomes.